Analisis Manajemen Risiko Operasional serta Keselamatan dan Kesehatan Kerja (K3) berbasis ISO 31000 pada AD Barbershop - Zaid Abdul Hamid; Dea Wisnu Ramdhani; Ahmad Ryansyah; Ari Assrishhan Sos Mantoro; Alfiana (Indo Publishing, 2025)
This study analyzes risk management in AD Barbershop, a grooming service operating two outlets in Bandung. The research aims to identify, assess, and treat operational and occupational health and safety risks that may affect service quality and business continuity. A qualitative descriptive single–case design was applied through semi-structured interviews, direct observation, and documentation review. Risk events were organized into a risk register and evaluated using the ISO 31000 framework and a 5×5 likelihood–impact matrix. The study identified 16 risks across hygiene, operations, utilities, and ergonomics. Recommended treatments emphasize queue control, standardized procedures, improved hygiene, and backup electricity solutions..